Return to the traumas: The literary depiction of war in the modern Ukranian and Polish novel - Pukhonska, Oksana (Slavia Centralis, 2021)
In the article the peculiarities of the interpretation of modern military discourse in the Ukrainian and Polish novel were analysed. The researching of the problem is concentrated on the novels of Volodymyr Lys’ Solo for Solomia and of Ignacy Karpowicz’s Sonka. The main reason of the research is the changing of the paradigm in the perception of World War II by the posterities of the victims of tragedy. The comparative way of analysing gives the possibility to reveal the specifics of the literary rethinking of the society’s traumatic experience with the help of the personal history in two cultural discourses.
Keywords: war; trauma; memory; identification; history; literature